Definitions The CONJUNCTION of two propositions p and q is written p ∧ q. It denotes “p and q”. The DISJUNCTION of two propositions p and q is written p ∨ q. It denotes “p or q”. The CONDITIONAL PROPOSITION is written p → q, is the proposition “if p then q”. p is the HYPOTHESIS or PREMISE and q is the CONCLUSION or CONSEQUENCE p and q are EQUIVALENT and write p ≡ q if they always have the same truth value. The BICONDITIONAL PROPOSITION p ↔ q is “p if, and only if, q”. It is true when p and q have the same truth values and is false otherwise (exactly the same) Initial p→q ≡ ¬p ∨ q Contrapositive ¬q →¬p ≡ ¬p ∨ q Converse q→p ≡ ¬p ∨ q Inverse ¬p → ¬q ≡ ¬p ∨ q Commutative laws: p ∧ q ≡ q ∧ p; p∨q≡q∨p Associative laws: (p ∧ q) ∧ r ≡ p ∧ (q ∧ r); (p ∨ q) ∨ r ≡ p ∨ (q ∨ r) Distributive laws: p ∧ (q ∨ r) ≡ (p ∧ q) ∨ (p ∧ r) p ∨ (q ∧ r) ≡ (p ∨ q) ∧ (p ∨ r) Identity laws: p ∧ T ≡ p; p∨C≡p p ∧¬p = C; p ∨¬p = T Negation laws: Double negation laws: ¬(¬p) ≡ p Idempotent laws: p ∧ p ≡ p; p∨p≡p p ∧ C ≡ C; p∨T≡T ¬(p ∧ q) ≡ ¬p ∨ ¬q; ¬(p ∨ q) ≡ ¬p ∧ ¬q Universal bound laws: De Morgan’s laws: Absorption laws: p ∧ (p ∨ q) ≡ p; p ∨ (p ∧ q) ≡ p Negations of T and C: ¬C ≡ T; ¬T ≡ C We imagine the actions suggested by the quantifiers as being performed in the order in which the quantifiers occur. Reversing the order of the quantifiers can change the truth value of a statement unless the quantifiers are all universal or all existential. For example, “everyone loves someone” is translated into: ∀x∃y P(x,y) where P(x,y) is “x loves y.” However ∃y∀x P(x,y) is “there is someone who is loved by everyone”. ∀ ∀ ∃ ∃ x∃ y∃ x∀ y∀ y P(x, y) – For all x, there exist y such that P is true x P(x, y) – For all y, there exist x such that P is true y P(x, y) – There exist x such that for all y, P is true x P(x, y) – There exist y such that for all x, P is true To Prove: p → q Direct Proof: Start by assuming that p is true. Subsequent steps are constructed using various rules of inference, with the final step showing that q is true. Proof by Contraposition: Contrapositive of p → q is¬q →¬p and are equivalent. Begin by assuming that¬q is true, i.e. q is false and proceed to prove that¬p is true, i.e. p is false. This will prove that¬q →¬p is true. Because of equivalence, conclude that p → q is true. Proof by Contradiction: Start by assuming that P is false and arrive at a contradiction. Contradiction may be in form that goes against some of the assumptions or some absurd conclusion. The logic is as follows: We have prove that¬P → C is true. But C, being a contradiction, is false. Thus¬P is false and hence P is true. When P is of the form: ∀ x(P(x) → Q(x)), we proceed as follows: We assume that the negation is true, i.e.∃ x¬(P(x) → Q(x)) or equivalently, ∃ x P(x)∧ ¬Q(x). So we start by assuming there is an x for which P(x) is true and Q(x) is false. Eventually, arrive at a contradiction, usually (but not always), in the form that P(x) is false.